2018
DOI: 10.1161/jaha.117.006428
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Dilated Cardiomyopathy‐Associated LRRC10 (Leucine‐Rich Repeat–Containing 10) Variant Reveals LRRC10 as an Auxiliary Subunit of Cardiac L‐Type Ca 2+ Channels

Abstract: BackgroundGenetic causes of dilated cardiomyopathy (DCM) are incompletely understood. LRRC10 (leucine‐rich repeat–containing 10) is a cardiac‐specific protein of unknown function. Heterozygous mutations in LRRC10 have been suggested to cause DCM, and deletion of Lrrc10 in mice results in DCM.Methods and ResultsWhole‐exome sequencing was carried out on a patient who presented at 6 weeks of age with DCM and her unaffected parents, filtering for rare, deleterious, recessive, and de novo variants. Whole‐exome sequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 58 publications
3
26
0
Order By: Relevance
“…Complementary findings by Woon et al provide new mechanistic insights into regulation of LTCC gating by identifying LRRC10 as a novel auxiliary subunit . In a parallel study, LRRC26 proteins have been shown to modulate the gating of a large conductance Ca 2+ ‐activated K + (BK) channel by enhancing the allosteric coupling between voltage‐sensor activation and the channel's closed–open transition.…”
Section: New Insights Into the Regulatory Mechanisms For Cardiac E‐c mentioning
confidence: 87%
See 1 more Smart Citation
“…Complementary findings by Woon et al provide new mechanistic insights into regulation of LTCC gating by identifying LRRC10 as a novel auxiliary subunit . In a parallel study, LRRC26 proteins have been shown to modulate the gating of a large conductance Ca 2+ ‐activated K + (BK) channel by enhancing the allosteric coupling between voltage‐sensor activation and the channel's closed–open transition.…”
Section: New Insights Into the Regulatory Mechanisms For Cardiac E‐c mentioning
confidence: 87%
“…In an intriguing and comprehensive study by Woon and colleagues in the current issue of JAHA , the authors used whole exome sequencing to identify a homozygous recessive variant (I195T) in the LRR region of LRRC10 in a sporadic case of pediatric DCM. Comprehensive mechanistic study reveals the unique roles of LRRC10 in the modulation of cardiac LTCC.…”
Section: Novel Auxiliary Subunit Of Cardiac Ltcc and Its Roles In Dilmentioning
confidence: 99%
“…; Woon et al . ). Cav3 has also been shown to interact with a subpopulation of the L‐type Ca 2+ channels localized to caveolae, and these channels are distinct from the subpopulation of L‐type Ca 2+ channels present in the dyadic regions in ventricular myocytes that play a critical role in excitation–contraction coupling (Balijepalli et al .…”
Section: Discussionmentioning
confidence: 97%
“…There are multiple splice variants for all of the channel subunits expressed in the heart, with at least 18 different Ca v β isoforms identified in the human ventricle (Foell et al 2004). There are other proteins besides the classical subunits which associate with Ca v 1.2 channels to fine tune channel function, including calmodulin (CaM), which plays an essential role in mediating CDI, and the more recently recognized cardiac-specific LRRC10, which modulates channel gating (Peterson et al 1999;Woon et al 2017). Cav3 has also been shown to interact with a subpopulation of the L-type Ca 2+ channels localized to caveolae, and these channels are distinct from the subpopulation of L-type Ca 2+ channels present in the dyadic regions in ventricular myocytes that play a critical role in excitation-contraction coupling .…”
Section: Lqt9 Cav3 Mutations and I Calmentioning
confidence: 99%
“…Cytosolic Ca 2+ is returned to basal diastolic levels by reuptake back into the SR through the sarco ER ATPase (SERCA2a), and to a lesser extent, extrusion of Ca 2+ outside the cell by the Na + /Ca 2+ -exchanger (NCX) (MacLennan and Kranias, 2003;Lytton, 2007; Figure 2). Cardiomyocyte electrophysiological properties are highly regulated by a number of ion channels, pumps, and auxiliary proteins each optimally positioned within the cardiomyocyte to impart precise spatiotemporal control of intracellular Na + , Ca 2+ , and K + ion concentrations (MacLennan and Kranias, 2003;Lytton, 2007;Fuller et al, 2013;Brody and Lee, 2016;Edokobi and Isom, 2018;Woon et al, 2018). Here we will highlight S-acylation-dependent mechanisms controlling ion channel homeostasis and excitation-contraction coupling in cardiomyocytes.…”
Section: Myocardial Electrophysiologymentioning
confidence: 97%